2006
DOI: 10.1115/1.2711471
|View full text |Cite
|
Sign up to set email alerts
|

A 300kW Solar Chemical Pilot Plant for the Carbothermic Production of Zinc

Abstract: In the framework of the EU-project SOLZINC, a 300-kW solar chemical pilot plant for the production of zinc by carbothermic reduction of ZnO was experimentally demonstrated in a beam-down solar tower concentrating facility of Cassegrain optical configuration. The solar chemical reactor, featuring two cavities, of which the upper one is functioning as the solar absorber and the lower one as the reaction chamber containing a ZnO/C packed bed, was batch-operated in the 1300–1500 K range and yielded 50 kg/h of 95%-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(25 citation statements)
references
References 26 publications
0
24
0
1
Order By: Relevance
“…B. auch die solarthermische Rückgewinnung von Zink aus Zinkoxid, das in größerem Umfang in Zink/Luft‐Batterien anfällt, angeführt werden. Dazu wird das zu recycelnde Material im Festbettreaktor bei 1000 – 1300 °C reduziert .…”
Section: Nutzung Chemischer Reaktionen Zur Speicherung Thermischer Enunclassified
“…B. auch die solarthermische Rückgewinnung von Zink aus Zinkoxid, das in größerem Umfang in Zink/Luft‐Batterien anfällt, angeführt werden. Dazu wird das zu recycelnde Material im Festbettreaktor bei 1000 – 1300 °C reduziert .…”
Section: Nutzung Chemischer Reaktionen Zur Speicherung Thermischer Enunclassified
“…In the case of the solar lime, Meier et al [34][35][36][37] designed a kiln furnace heated indirectly by means of a system of rotatory tubes, and they concluded that the process could be used to produce high quality lime, as the solar lime price would be twice the price of the conventional lime. In the case of the zinc (zinc can be used in water splitting to produce H 2 , or to use zinc as combustible in batteries and combustible cell), several research projects have allowed to build (EU-SOL-ZINC, 0.3 MW solar plants for the production of 50 kg Zn/h, [38]) and design several demonstration plants (for instance, a 5 MW conceptual design of demonstration plant, 1700 kg Zn/h; and, other of 30 MW to produce 10,000 kg Zn/h [39]). These two research lines allows us to think that if the process is deeply studied, concentrated solar energy could be used in the production of steel (as significant quantities of steel could be produced every day), and this process could be used in countries with abundance of solar energy, as costs could be reduced and the environmental impact could be minimized (as indicated).…”
Section: Potential Advantages Of Solar Energy: Reduction In Both Co 2mentioning
confidence: 99%
“…23 These studies formed the precursor work for the present multi-national project called Solzinc, carried out jointly by Switzerland, France, Sweden, and Israel, and aimed at developing solar reactor technology for the solar carbothermal production of zinc. 24 The 300 kW solar pilot plant has been successfully erected at the Weizmann Institute of Science in Rehovot, Israel.…”
Section: Zinc Productionmentioning
confidence: 99%